Hypothermia yields favourable cardiac energetics in experimental ischemia/reperfusion – insights from non-invasive pressure-volume loops by CMR. (3rd October 2022) - Berg, J; Jablonowski, R; Nordlund, D; Ryd, D; Heiberg, E; Carlsson, M; Arheden, H
Abstract: Background/Introduction: In experimental studies, mild hypothermia (<35°C) has reduced infarct size [1], potentially through reduced reperfusion injury [2], but human trials have been ambiguous [3]. Furthermore, a pressure-volume (PV) loop framework is the gold standard for assessing cardiac performance, but the invasive approach limits its clinical use. Therefore, we used a porcine model of ischemia/reperfusion with cardiovascular magnetic resonance (CMR) imaging throughout one week to acquire non-invasive PV loops. Purpose: To quantify the cardioprotective effects of hypothermia at reperfusion by serial CMR imaging in a perspective of cardiac energy and mechanics. Methods: Normothermia and Hypothermia groups (n=7+7 pigs) were imaged with CMR at baseline and subjected to 40 minutes of normothermic ischemia by catheter intervention. Thereafter, the Hypothermia group was rapidly cooled (<35°C) for 5 minutes before reperfusion. Additional imaging at two hours, 24 hours, and seven days were used to assess ventricular volumes and ischemic injuries. Infarct size was determined by high-resolution ex-vivo T1-weighted images. Results: Figure 1 shows that stroke volume (SV: p=0.029; Friedmans test) and ejection fraction (EF: p=0.068) were notably reduced post-reperfusion in the Normothermia group. In contrast, the decreases were ameliorated in the Hypothermia group (SV: p=0.77; EF: p=0.13). Mean arterial pressure (MAP) was stable in the Normothermia group (p=0.77) but dropped two hours post-reperfusion in hypothermic animals (p=0.007). Over one week, both groups experienced the same decrease and partial recovery pattern for stroke work, external power, and ventricular-arterial coupling. Still, the adverse effects from ischemia were generally attenuated in the Hypothermia group. Although not significant, ischemia/reperfusion caused smaller infarcts in the Hypothermia group (10±8% vs 15±8%; p=0.32). The change in PV loop variables from baseline to 24 hours was compared with infarct size for each group. Though statistical power was limited, the general trend in analyses of covariance indicated that hypothermia has cardioprotective properties incremental to reducing infarct sizes (Figure 2), such as higher external power (p=0.061) and lower arterial elastance (p=0.015). Conclusion: Using non-invasive PV loops by CMR, we observed that mild hypothermia before reperfusion results in favourable cardiac energetics that alleviates the heart's work after an ischemia/reperfusion injury during the first week. This study suggests that hypothermia has cardioprotective properties, incremental to reducing infarct size. The primary cardioprotective mechanism was likely an afterload reduction unloading the injured left ventricle. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Swedish Heart-Lung FoundationThe Medical Faculty of Lund University (ALF)